1991
DOI: 10.1063/1.858173
|View full text |Cite
|
Sign up to set email alerts
|

Wake mechanics for thrust generation in oscillating foils

Abstract: LETTERSThe purpose of thtk Letters section is to provide rapid dissemination of important new results in theJields regularly covered by Physics of Fluids A. Results of extended research should not be presented as a series of letters in place of comprehensive articles. Letters cannot exceed three printed pages in length, including space allowed for title, figures, tables, references and an abstract limited to about 100 words. There is a three-month time timit, from date of receipt to acceptance, for processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
266
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(292 citation statements)
references
References 8 publications
22
266
1
1
Order By: Relevance
“…The experimental investigation of Anderson et al [11] showed that optimum propulsive efficiencies were obtained within an approximate range of Strouhal numbers 0.2-0.4. This range coincides with that presented by Triantafyllou et al [12] for observed fish and cetaceans swimming at or near their maximum observed speed. However, Young and Lai [13] concluded through a numerical study that Strouhal number alone was insufficient to characterize the efficiency of flapping foil propulsion.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The experimental investigation of Anderson et al [11] showed that optimum propulsive efficiencies were obtained within an approximate range of Strouhal numbers 0.2-0.4. This range coincides with that presented by Triantafyllou et al [12] for observed fish and cetaceans swimming at or near their maximum observed speed. However, Young and Lai [13] concluded through a numerical study that Strouhal number alone was insufficient to characterize the efficiency of flapping foil propulsion.…”
Section: Introductionsupporting
confidence: 77%
“…Therefore, a lift production along with thrust is expected. In accordance with Equation (12), high efficiencies are observed in general for low Strouhal numbers, just before a C d ≥ 0 value is observed. These cases are in general designated as Category D.…”
Section: Velocity Deficit Profiles From Dpiv Imagessupporting
confidence: 61%
“…This Strouhal number is also near the range in which aquatic animals are known to swim (Triantafyllou et al 1991(Triantafyllou et al , 1993, forming a reverse Kármán pattern in the symmetry plane (Triantafyllou & Triantafyllou 1995). The significant change in performance between the low-and moderate-Reynoldsnumber cases is attributed to the relative magnitude of surface pressures from which thrust is generated, to viscous shear stresses which primarily produce drag (note that separated flows may produce small shear stresses that make a positive contribution to the thrust).…”
Section: Sensitivity Of Wake Structure To Reynolds Numbermentioning
confidence: 87%
“…Other factors, such as stiffness of the tail, swimming frequency and Strouhal number may be responsible for differences in wake structure [32,33].…”
Section: Discussionmentioning
confidence: 99%